Mobilography is a new phenomenon in the media - Serdali, Б. (Bulletin of L.N. Gumilyov Eurasian National University. JOURNALISM Series, 2023)
Today's media not only spread information, but also create interesting news that we can watch, listen to and read by viewing our audiovisual creations using our small mobile devices. This trend usually coincides with modern searches in the media sphere. Therefore, mobile journalism is gaining momentum not only abroad, but also in Kazakhstan. Young journalists who are passionate about the possibilities of new media, and those who want to work in the field of media in the future, react especially to this. They prove that, as before, there is no need to sit in front of large portable computers, monitors. Through their small mobile devices in their hands, they can shoot, edit and create high-quality media products. Our article says that mobilography is one of such modern phenomena. We can say that this is a new direction in electronic journalism. At first it appeared as a genre of photography and in a short time gained popularity among millions of amateur photographers. And this was followed by skeptical interest, creating an image among photography professionals. Now, in this process, television filming has also begun to be done.